(untitled) (The Research of Medical Science Review, 2025)
Background: Warm-up and cool-down routines are essential components of strength training. Despite their importance in preventing injuries and enhancing performance, there is limited data on the current practices among strength trainers in Punjab. Objective: This research aimed to assess strength trainers' knowledge, frequency, types, duration, perceived importance, and source of information regarding warm-up and cool-down. Methodology: An observational study was conducted among 600 male strength trainers in different gyms of Punjab. Data were collected through self-designed written questionnaires, and analysis was performed using SPSS. Results: 62.7% of trainers are aware of warm-up; 49.0% always engage, 50.2% spend 5- 10 mins. Walking/jogging/running (30.6%) and stretching (25.9%) are the most popular warm-up activities. 67.9% of trainers consider warm-up highly important. 50% of trainers engage in cool-down. Deep breathing (24.7%) and rest (23.9%) are common techniques for cool-down. 55.5% cool down for a duration of 5-10 mins. 40% consider cool-down highly important while 39% consider it of intermediate importance. Conclusions: There is high awareness and engagement in warm-up among trainers, perceived as highly important with a common duration of 5-10 mins. Walking/jogging and stretching are common warm-up techniques. Cool-down engagement is lower and not considered as highly important. The common duration for cool-down is 5-10 mins; rest and deep breathing are common techniques.